the GOSIP MYTH IN KONTRAKAN REMPONG EPISODE: 111 and 131 (BARTHES FRAME) - Simorangkir, imelda Malawaty (FKIP, Universitas Banten Jaya, 2024)
object. The researchers were interested in examining the Kontrakan Rempong vlog film because we witnessed the phenomena of ladies whose passion is gossip, exposing the humiliation of others. The purpose of this research is to look into the gossip myth in Kontrakan Rempong. Gossip serves a purpose that extends beyond the scope of interpersonal relationships; consequently, gossip serves societal purposes. The descriptive qualitative method was employed in this investigation, along with data reduction strategies. The researchers employed semiotics in their research is from Roland Barthes to find hidden meanings (myths) from the gossip conveyed in these two films. As the conclusion of this research is to prove that a film or sitcom is a picture of what is happening in society. Apart from that, this research aims to prove that people who like to gossip are people who lack the knowledge to use their free time, and gossip is portrayed by women in Kontrakan Rempong, because not all gossip is a falsehood generated by human envy and jealousy.